2000
DOI: 10.1021/ja0006649
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Olefin Epoxidation Catalyzed by Molybdenum Diperoxo Complexes:  Quantum-Chemical Calculations Give an Answer to a Long-Standing Question

Abstract: Quantum-chemical calculations at the B3LYP level have been carried out to elucidate the reaction mechanism of the epoxidation of ethylene with the molybdenum diperoxo complex MoO(O2)2OPH3. All relevant transition states and intermediates which belong to the reaction pathways suggested by Mimoun and by Sharpless were optimized. The calculations show that there is no reaction channel from the ethylene complex to the putative metalla-2,3-dioxolane intermediate as suggested by Mimoun. There is a transition state f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 76 publications
9
89
1
3
Order By: Relevance
“…[27] The theoretically predicted energies of the transition states and the calculated intrinsic reaction coordinates show that the oxygen transfer takes place in a single-step reaction via a direct attack of the alkene to the peroxo group as proposed by Sharpless, [28] thus ruling out Mimouns metalla-2,3-dioxolane model. [26] We initially evaluated the epoxidation of unprotected glucal (1) under similar conditions to those previously explored, [23] using two molybdenum catalysts in polar solvents such as water and methanol and using different oxidizing reagents.…”
Section: Resultsmentioning
confidence: 77%
“…[27] The theoretically predicted energies of the transition states and the calculated intrinsic reaction coordinates show that the oxygen transfer takes place in a single-step reaction via a direct attack of the alkene to the peroxo group as proposed by Sharpless, [28] thus ruling out Mimouns metalla-2,3-dioxolane model. [26] We initially evaluated the epoxidation of unprotected glucal (1) under similar conditions to those previously explored, [23] using two molybdenum catalysts in polar solvents such as water and methanol and using different oxidizing reagents.…”
Section: Resultsmentioning
confidence: 77%
“…[3][4][5][6][7][8][9][10] They are widely used in stoichiometric as well as catalytic oxidation in organic and biochemistry, 11 for example, in the oxidation of thioanisole, 12,13 methylbenzenes, 14 tertiary amines, alkenes, alcohols, 15,16 bromide 17 and also in olefin epoxidations. [18][19][20][21][22] There has been a continuous upsurge in interest in peroxo compounds of vanadium since it has been demonstrated that vanadate and peroxovanadates are capable of inhibiting the hydrolysis of phosphoproteins [23][24][25][26] and exhibit insulin-like properties. [27][28][29][30][31] The exact mechanisms by which peroxovanadates carry out these functions are yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…1 They are widely used in stiochiometric as well as catalytic oxidation in organic and biochemistry, 2 for example in the oxidation of thioanisole, 3,4 methylbenzenes, 5 tertiaryamines, alkenes, alcohols, 6,7 bromide 8 and also in olefin epoxidations. [9][10][11][12][13] They also act as isomerisation catalysts for some allylic alcohols and have been applied to bleaching processes.…”
Section: Introductionmentioning
confidence: 99%